Markedly Reduced White Adipose Tissue and Increased Insulin Sensitivity in Adcyap1-Deficient Mice - Shuhei Tomimoto; Tatsuya Ojika; Norihito Shintani; Hitoshi Hashimoto; Ken-ichi Hamagami; Kazuya Ikeda; Masanori Nakata; Toshihiko Yada; Yusuke Sakurai; Takeshi Shimada; Yoshiko Morita; Chie Ishida; et al. (Elsevier, 2008)
Pituitary adenylate cyclase-activating polypeptide (PACAP) is a neuropeptide implicated in several metabolic functions, including insulin secretion and sympathoadrenal activation. To clarify the roles of PACAP in maintenance of whole-body glucose and lipid homeostasis, the impact of the deletion of PACAP on glucose homeostasis, body weight, and adipose tissue mass was examined by comparing mice lacking the Adcyap1 gene encoding PACAP (Adcyap1−/−) with wild-type littermate controls. Adcyap1−/− mice showed significant hypoinsulinemia, although being normoglycemic, and lower body weight as well as reduced food intake. They also showed greatly reduced white adipose tissue mass, in which the mRNA expression of adipocyte fatty acid-binding protein (aP2), a marker of adipocyte differentiation, was decreased. Glucose and insulin tolerance tests revealed increased insulin sensitivity in Adcyap1−/− mice. In accordance with these observations, plasma levels of resistin, an adipocytokine implicated in insulin resistance, were decreased in Adcyap1−/− mice. After a high-fat dietary challenge for six weeks, Adcyap1−/− mice still showed lower body weights and increased insulin sensitivity. These results indicate the crucial roles of PACAP in energy metabolism, including lipid metabolism, and in the regulation of body weight, raising the possibility that the PACAP-signaling pathway that favors energy storage could be a therapeutic target for obesity. Keywords:: adipose tissue, body weight, insulin sensitivity, pituitary adenylate cyclase-activating polypeptide (PACAP), resistin